The Influence Of Various Toll Accident Factors For The Wound Suffered By The Victim Using C4.5 Algorithm - Andi Azhar Mustary Husein (Universitas Muhammadiyah Sidoarjo, 2022)
The toll road is the main road that connects one city to another, used to speed up the journey of public and corporate vehicles. However, toll roads are no longer safe because of human negligence who does not obey existing regulations, resulting in victims. The C4.5 algorithm is one of the algorithms used to form a decision tree based on training data. This algorithm is a very powerful and well known classification and prediction method. The process of processing accident data in toll road management companies has not used data mining methods. So it is necessary to create a data mining method using the C4.5 algorithm. With this method, it is expected to be able to assist toll road managers in dealing with existing accidents based on the results of data processing using this method. The results of this study are the results of the prediction presentation, where using manual calculations the truth rate is 86% and the error rate is 14%, for calculations using the Weka application the truth is 79% and the error rate is 21%.